Art and Truth (Iter, 2022)
The author starts from the definition o f truth as 'adaequatio intellectusad rem'. Where 'intellectus' is understood as 'logos', 'res' as the thing itself,upon which falls the saying of the 'logos', and 'adequatio' as the "coincidence "or "equating" of that which is expressed in a propos al with the actual beingof the thing. Upon its being expressed, the thing's self enters a realm o f light,and man perceives it because he is "radically and entitively" touched by theone and whole being. The truth of the statement, if we understand it fromthat original dimensión which makes it possible, is quite cióse to the truth inart. Art is truth in its full execution. The language of art "truthens", its wordsummons things and invites them to enter "the clearing in the being". Whenthis being is brought forward, we talk about beauty. Beauty is the splendor o fthe being's truth in the hollows of feeling, and this is the most sublime way o fhuman intellection.
Keywords: Art, truth, beauty, feeling, intellection